Comparison of endoscopic transcanal myringoplasty and endoscopic type I tympanoplasty in repairing medium-sized tympanic perforations. Issue 6 (December 2017) - Tseng, Chih-Chieh; Lai, Ming-Tang; Wu, Chia-Che; Yuan, Sheng-Po; Ding, Yi-Fang
Abstract: Objective: The tympanomeatal flap elevation technique has been used in tympanoplasty for decades; however, this procedure has disadvantages. In recent years, endoscopic transcanal myringoplasty (ETM) has been increasingly practiced and has yielded positive results.This study compares the efficacy of ETM and endoscopic type I tympanoplasty (ETT) in repairing medium-sized perforations of the tympanic membrane. Methods: This retrospective medical record review included patients undergoing surgery for medium-sized perforations of the tympanic membrane from January 1, 2013 to August 1, 2015. We divided our patients into 2 groups: the ETM group and ETT group. The main outcome measure was comparison of the graft take rates and hearing results between ETM and ETT. Results: A total of 113 patients were enrolled in this study; of these patients, 64 underwent ETM and 49 received ETT. The overall graft take rates and improvement of air–bone gaps were comparable between the groups. However, the patients in the ETM group had shorter operative times and fewer follow-up visits over 3 months than those in the ETT group did. Conclusion: We recommend that ETM (instead of ETT) be used for repairing medium-sized perforations of the tympanic membrane.